PENGARUH PERPUTARAN MODAL KERJA, PERPUTARAN KAS, PERPUTARAN PIUTANG, DAN PERTUMBUHAN KOPERASI TERHADAP PROFITABILITAS - Wirasari, Ni Putu Putri; Sari, Maria M. Ratna (E-Jurnal Akuntansi; Vol 17 No 2 (2016), 2016)
The purpose of this study was to determine the effect of working capital turnover, turnover of cash, accounts receivable turnover and growth of cooperatives on the profitability of business cooperatives in South Denpasar District Year 2012-2014. The study was conducted on business cooperatives in South Denpasar District Year 2012-2014. The sample in this study are the financial statements of business cooperatives 24 years from 2012 to 2014. The analysis technique used is multiple linear regression. Based on the results of analysis show that the level of working capital turnover, perputran cash, accounts receivable turnover and growth of cooperatives positive effect on profitability. The effect of variable working capital turnover, turnover of cash, accounts receivable turnover and profit turnaround to profitability has a value of determination of 49.5 per cent while the remaining 50.5 percent is influenced by other variables not included in the research model.
Keywords: Working Capital Turnover, turnover Cash, Accounts Receivable Turnover, Cooperative Growth, Profitability